The Impact of Audit Committee and Internal Audit towards Financial Statement Quality: External Audit and Corporate Governance as Intervening Variables - ., Islahuzzaman; ., Syafdinal; Arsalan, Syakieb; Lisa Aryanti, Maya (International Journal of Engineering and Technology, 2018)
A financial statement is a crucial matter since its quality is declining. This research developed and tested a theoretical model which identified factors directly or indirectly contributing to the financial statement quality, namely audit committee and internal audit; meanwhile, external audit and corporate governance were considered as antecedent factors having impact on the report. The objective of the research is to gain insight on such factors. The objective of the research is to gain insights on factors that affect such reports. The findings showed consistent evidence supporting the theoretical model. They also showed how AC and IA simultaneously and partially impacted the quality of financial statements (QFS). AC and IA directly or indirectly affect the quality of the financial statement. They also have indirect effects through CG and EA in enhancing the quality to 77%.Â